iVoca Application as a Tool to Learn English Vocabulary : Students’ Perception - Tien Rafida; Novia Amanda (Universitas Islam Negeri Palopo, 2025)
The development of artificial intelligence (AI)-based technology is accelerating, making the learning process easier and increasing its effectiveness. This study aims to evaluate the success of the iVoca application in improving English vocabulary mastery and to understand students' perceptions of its use. The methods used include questionnaires and interviews with 10 twelfth-grade students at a high school in Medan. The results show that 78.6% of students stated that iVoca made vocabulary learning less boring thru word game features, daily challenges, and visual and audio media that support understanding. Additionally, 71.4% of students felt more focused and motivated while using this application, while 75% were willing to recommend it to their friends. The findings also revealed major limitations, such as dependence on internet connectivity and limited media variety. These results indicate that iVoca is effective in increasing learning motivation and vocabulary mastery in the context of online learning. This research provides important insights into the development of educational technology that is more responsive to student needs, with practical implications for improving technology-based learning media to be more inclusive and adaptive.